Repeated nonanesthetic malignant hyperthermia reactions in a child. Issue 12 (26th August 2016) - Cummings, Theresa; Der, Tara; Karsli, Cengiz
Summary: A series of life‐threatening nonanesthetic‐related MH reactions in a child was the inspiration for a proactive, novel solution allowing for early prehospital, potentially lifesaving intravenous dantrolene administration. Multidisciplinary collaboration is essential and parent education must be comprehensive and ongoing. This case underlines the importance of considering nonanesthetic MH susceptibility in the child who has a history of unspecified myopathy and who presents with fever and total body stiffness.